Knowledge and Awareness about Personal Hygiene among the Caregivers of the Children of Acute Watery Diarrhoea attending in a Tertiary Care Hospital - Saha, Gouri; Amin Chowdhury, Muhammad Jabed Bin; Wadia, Nevis; Biswas, Shantanu (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Personal hygiene is very important during the management of acute watery diarrhea patients. Objective: The objective of the study was to assess the knowledge and awareness about personal hygiene among the caregivers of the patient of acute watery diarrhoea. Methodology: This Descriptive type of cross-sectional study was conducted in the Department of Paediatrics at Chittagong Medical College Hospital, Chittagong, Bangladesh from 20th March 2015 to 19th September 2015 for a period of six months. All caregivers were the respondents of children with up to 3 years old suffering from acute watery diarrhoea attended in Paediatrics unit of Hospital. This included persons residing in urban and semi-urban areas around Chittagong city, as well as persons transferred from hospitals in rural areas of the country. Sample was selected from the population by purposive sampling technique. The details of socio-demographic characteristics, including age, different questions of awareness and knowledge were recorded. Results: A total number of 100 patients were taken as sample for study. Mean age of the patient were 18.05 ± 6.78 month. Over half of the respondents (52%) make answered that personal hygiene means to remain neat and clean. Some of the caregivers (32.0%) maintain personal hygiene by clean hand properly with soap after using toilet. About 30.0% respondents reported that they do not know what to do before taking meal or feed the baby. Many of the respondents (45%) knew about the use of sanitary latrine and (45%) use of clean latrine is mandatory to maintain environmental hygiene. Majority of caregiver (38%) answered that waste products of child’s may be harmless. Conclusion: In conclusion the knowledge and awareness about personal hygiene among the caregivers of the children presented with acute watery diarrhea is not satisfactory. Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):52-56